Implementation of Base Station Communication Systems on Wheels Football Robots - Agitasani, Revi; Puriyanto, Riky Dwi (Signal and Image Processing Letters, 2022)
In the wheeled soccer robot contest competition, you have to prepare a strategy to win the race. The strategy used is a communication system. The communication system on the wheeled soccer robot has an important role during the match. This research will discuss the implementation of the GUI on the Base Station using the processing 3 application in its manufacture and using the Java language and analyzing data transmission. The use of the GUI is shown to make it easier to control robots during matches and minimize human work. The communication system used uses multicast with the UDP (User Datagram Protocol) protocol. Based on the results of research using the UDP protocol, the data transmission carried out by the GUI at the Base Station can function as a robot sending data. The resulting average delay is the farther the distance the more the average delay generated. The success rate of delivery is 100%.